Positive allosteric modulation of AMPA receptors via PF4778574 leads to reduced demyelination and clinical disability in experimental models of multiple sclerosis - Sindi, Mustafa; Dietrich, Michael; Klees, Diana; Gruchot, Joel; Hecker, Christina; Silbereis, John; Issberner, Andrea; Hartung, Hans-Peter; Ruck, Tobias; Stark, Holger; Kurz, Thomas; Küry, Patrick; et al. (Frontiers in Immunology, 2025)
IntroductionMultiple Sclerosis (MS), a debilitating central nervous system (CNS) disorder, is characterized by inflammation, demyelination, and neuronal degeneration. Despite advancements in immunomodulatory treatments, neuroprotective or restorative strategies remain inadequate. Our research is focusing on the potential of the positive allosteric modulator of AMPA receptors (AMPA-PAM), PF4778574, in addressing MS symptoms.MethodsWe utilized the MOG35-55 induced experimental autoimmune encephalomyelitis (EAE) model in C57BL6J mice to examine PF4778574’s therapeutic and prophylactic efficacy. Our comprehensive approach included clinical scoring, optical coherence tomography (OCT), optomotor response (OMR) and histological assessments. Additionally, we explored the effects of PF4778574 in comparison and in combination with the immunomodulatory agent fingolimod, and investigated the impact on Cuprizone induced toxic demyelination.ResultsProphylactic administration of PF4778574 showed notable improvement in clinical EAE indices and reduction in neuronal loss. While it did not diminish microglial activity, it reduced demyelinated areas in optic nerves and in the corpus callosum. Both PF4778574 and fingolimod significantly enhanced clinical EAE scores and decreased demyelination. However, their combination did not yield additional benefits. In the cuprizone model, PF4778574 increased oligodendrocyte precursor and mature myelin-forming cells, suggesting a pro-remyelinating effect.DiscussionPF4778574 demonstrates promise in mitigating EAE effects, especially in terms of clinical disability and demyelination. These results suggest AMPA-PAMs as potential targets of interest for MS treatment beyond immunomodulatory approaches.